The role of universities in fostering entrepreneurship: strategies and best practices - Aranibar Ramos, Edgar Romario (2023)
Today, entrepreneurship is crucial for economic growth and innovation. Therefore, we seek to analyze the role of universities in fostering entrepreneurship and to learn about strategies and good practices to promote entrepreneurship among students. To this end, a multimodal systematic review was conducted. The results highlight that integrating entrepreneurship into the curriculum, providing financial support and access to resources, establishing incubators and co-working spaces, networking with industry and local entrepreneurial ecosystems, and offering mentoring and business advice are effective strategies to promote entrepreneurship among university students. In addition, five key elements are identified to create an enabling environment for successful entrepreneurship: fostering an entrepreneurial culture, providing education and training, offering financial support, and establishing partnerships for mentoring and business advice. It recommends allocating resources, implementing mentoring programs, fostering interdisciplinary cooperation, knowledge transfer and collaboration with business and civil society, and continuously evaluating and improving entrepreneurship policies. In short, it offers a comprehensive view of the role of universities in promoting entrepreneurship and provides recommendations for its promotion.